PICU Autopsies: Rates, Patient Characteristics, and the Role of the Medical Examiner*. Issue 12 (December 2018) - Basu, Sonali; Holubkov, Richard; Dean, J. Michael; Meert, Kathleen L.; Berg, Robert A.; Carcillo, Joseph; Newth, Christopher J. L.; Harrison, Rick E.; Pollack, Murray M.
Abstract : Objectives: Autopsy rates in North American Children's hospitals have not been recently evaluated. Our objectives were 1) to determine the autopsy rates from patients cared for in PICUs during a portion of their hospital stay, 2) to identify patient characteristics associated with autopsies, and 3) to understand the relative role of medical examiner cases. Design: Secondary analysis of data prospectively collected from a sample of patients ( n = 10, 078) admitted to PICUs affiliated with the Collaborative Pediatric Critical Care Research Network between December 2011 and April 2013. Setting: Eight quaternary care PICUs. Patients: Patients in the primary study were less than 18 years old, admitted to a PICU and not moribund on PICU admission. Patients included in this analysis were those who died during their hospital stay. Interventions: None. Measurements and Main Results: Sociodemographic, clinical, hospital, and PICU data were compared between patients who had autopsies conducted and those who did not and between medical examiner and nonmedical examiner autopsies. Of 10, 078 patients, 275 died of which 36% ( n = 100) had an autopsy performed. Patients with cancer who died were less likely to receive autopsies ( p = 0.005), whereas those who died after trauma or cardiac arrest had autopsies performed more often ( p < 0.01). Autopsies were more common in patients with greater physiologic instability at admission ( p < 0.001), and those who received more aggressive PICU care. Medical examiner cases comprised nearly half of all autopsies ( n = 47; 47%) were conducted in patients presenting with greater physiologic instability ( p < 0.001) and more commonly after catastrophic events such as cardiac arrest or trauma ( p < 0.001). Conclusions: In this first multicenter analysis of autopsy rates in children, 36% of deaths had autopsies conducted, of which nearly half were conducted by the medical examiner. Deaths with autopsy are more likely to be previously healthy children that had catastrophic events prior to admission.